Lamp Malfunction Detection System - Azra’i, Ahmad Amin Amri; Ismail, Nurulhuda (Evolution in Electrical and Electronic Engineering, 2024)
A critical facility like a hospital, the reliable operation of light fixtures is crucial. This study aimed to develop a lamp malfunction detection system to ensure timely maintenance and prevent disruptions. The system utilized LDR sensors to sense the presence of light and voltage sensors to detect voltage in the wiring circuit to monitor lamp conditions and identify faults. Inputs from current and voltage sensors were processed by an ESP32 microprocessor, which communicated the status to a Visual Basic (GUI) interface. The interface visually displayed lamp conditions and provided alerts for malfunctions. Additionally, the ESP32's Wi-Fi module,  integrated with the Blynk cloud platform, was used to notify the person in charge (PIC) via phone messages. The system was tested and successfully detected the status of lamps, distinguishing between 'on,' 'off,' and 'broken' states. Despite this, the interface consistently reported accurate lamp statuses, validating the communication protocols and data handling mechanisms. The final objective of alerting the PIC through the Blynk Platform was achieved, ensuring immediate attention to malfunctions. Thissystem enhances the maintenance department's ability to maintain essential electrical equipment efficiently, ensuring seamless operations in critical facilities.